AN AUTOPSY STUDY ON HUMAN BRAIN-LIVER WEIGHT RATIO IN BENGALEE POPULATION (Journal of Forensic Medicine & Toxicology, 2025)
Human organ weight differs with age and sex of an individual. Weighing of organs at autopsy is not merely an exercise but has great medicolegal importance. It can hint at pathological changes occurring in the organ which can help in interpreting opinion regarding cause of death in various pathological conditions3. The study was conducted to determine the effect of age of the subject on the weight of the organs and the factors influencing the weight ratio of the organs. A descriptive cross-sectional study was carried out over a period of 18 months i.e. from 1st Jan 2017 to 31st July 2018 in the Department of Forensic Medicine and Toxicology, R.G. Kar Medical College, Kolkata. A total of 266 medicolegal autopsies were taken and the brain, liver weight were measured and analysed. The study showed a significant correlation with effect of age and organ weight, as the age increases the weight of the organ increases with p.value less than 0.001 and the mean weight ratio of brain and liver also increases according to increase in age in both males and females.
Keywords: Brain weight; Liver weight; Bengalee population